EFEKTIVITAS MEDIA PAPAN PINTAR UNTUK MENINGKATKAN KEMAMPUAN PEMBAGIAN BILANGAN BAGI ANAK TUNARUNGU - Muhammad Aldy Zuherman; Martias Z (Jurnal Penelitian Pendidikan Khusus, 2023)
ABSTRACTThis study discusses the effectiveness of smart board media to improve number sharing capabilities for class VIII deaf children. This research uses a type of research in the form of Single Subject Research with the A-B-A technique. The analysis technique used is graphical analysis. Results from 15 observations on three baseline conditions (A1) of 0%, 10%, 10%, 10%. In intervention (B) obtained 40%, 50%, 60%,60% 70%, 70%, 70%. Finally, on the baseline (A2) the results are 60%, 80%, 80%, 80%. The results of this study show that the ability to divide numbers increases after using smart board media in deaf children of class VIII /B at SLBN 1 PadangÂ